Prevalence, predictors, dynamic bone change, and treatment efficacy of osteoporosis among chronic obstructive pulmonary disease patients: a prospective cohort study - Kaenmuang, Punchalee; Keeratichananont, Warangkana; Geater, Sarayut Lucien; Chantamanee, Nicha; Srikaew, Piyaporn (Frontiers in Medicine, 2023)
Background: Osteoporosis is a silent chronic obstructive pulmonary disease (COPD) comorbidity that is often under-detected. We aimed to study the prevalence and potential predictors of osteoporosis in COPD. Dynamic changes in bone mass density (BMD) and treatment efficacy of bisphosphonate were also assessed.Methods: This prospective cohort study included COPD patients between January 2017 and January 2019. Demographics data, spirometric parameters, and C-reactive protein (CRP) were collected. Bone mineral density (BMD) at the lumbar spine (L2-4) and both femoral necks were measured after enrollment and the 12-month follow-up. Participants were categorized into three groups per the baseline BMD T-score: normal (≥-1.0), osteopenia (between -1.0 and -2.5), and osteoporosis (≤-2.5). In the osteoporosis group, alendronate 70 mg/week with vitamin D and calcium was prescribed.In total, 108 COPD patients were enrolled. The prevalence of osteoporosis and osteopenia were 31.5% and 32.4%, respectively. Advanced age, lower body mass index (BMI), history of exacerbation in the previous year, and high CRP levels were significant predictors of osteoporosis. After 12 months, 35.3% in the osteoporosis group reported new vertebral and femoral fractures, compared to none in the non-osteoporosis group (p<0.001). In the normal BMD and osteopenia groups showed a further decline in BMD after 12-month. Conversely, the osteoporosis group showed a statistically significant improvement in BMD after anti-resorptive treatment (p<0.001).The prevalence of osteoporosis was high in Thai COPD patients. Advanced age, lower BMI, history of exacerbation, and high CRP levels were potential predictors. A rapid decline in BMD was observed in COPD patients without treatment.